Hubungan Antara Kualitas dan Intensitas Dzikir Dengan Kelapangdadaan Mahasiswa - Fuad Nashori (Millah: Journal of Religious Studies, 2005)
The following article constitutes the result of research. This research aims to describe corelation the quality and intensity of dzikr and the tolerant attitudes of regular students and boarding school students. The indicators that used in this research is the scale of tolerant attitudes, that of dzikr quality and intencity. The subject of the research is 109 students. This research revealed that there is positive corelation dzikr quality and the tolerant attitudes of regular students and boarding school students. The contribution of dzikr quality to the-tolerant attitude is 41.5 %. There is a negative corelation dzikr intencity and the tolerant attitude of regular students and boarding school students.